New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa - Niedbała, Wojciech; Hugo-Coetzee, Elizabeth A.; Ermilov, Sergey G. (Zootaxa, 2019)
Notophthiracarus (Oribatida, Phthiracaridae) is a large genus of ptyctimous oribatid mites with species in Australasian, Ethiopian, Neotropical, Oriental and Subantarctic regions, mostly in tropical and subtropical areas. Herein, we describe two new species from the Western Cape of South Africa: Notophthiracarus sidorchukae Niedbała sp. nov. and Notophthiracarus spathulatus Niedbała sp. nov. Each is represented by adult specimens collected from soil in a coastal forest in the Kaaimansgat estuary, the only documented locality. These two bring the known South African fauna of Notophthiracarus to 31 species, all of which are either indigenous or endemic. A review of distributional data shows that within South Africa most species have been recorded from southern, eastern and northeastern parts, and are most prevalent near the coast, where woody vegetation dominates.